Intrinsic local destabilization of the C‐terminus predisposes integrin α1 I domain to a conformational switch induced by collagen binding. (1st August 2016) - Nunes, Ana Monica; Zhu, Jie; Jezioro, Jacqueline; Minetti, Conceição A.S.A.; Remeta, David P.; Farndale, Richard W.; Hamaia, Samir W.; Baum, Jean
Abstract: Integrin–collagen interactions play a critical role in a myriad of cellular functions that include immune response, and cell development and differentiation, yet their mechanism of binding is poorly understood. There is increasing evidence that conformational flexibility assumes a central role in the molecular mechanisms of protein–protein interactions and here we employ NMR hydrogen–deuterium exchange (HDX) experiments to explore the impact of slower timescale dynamic events. To gain insight into the mechanisms underlying collagen‐induced conformational switches, we have undertaken a comparative study between the wild type integrin α1 I and a gain‐of‐function E317A mutant. NMR HDX results suggest a relationship between regions exhibiting a reduced local stability in the unbound I domain and those that undergo significant conformational changes upon binding. Specifically, the αC and α7 helices within the C‐terminus are at the center of such major perturbations and present reduced local stabilities in the unbound state relative to other structural elements. Complementary isothermal titration calorimetry experiments have been performed to derive complete thermodynamic binding profiles for association of the collagen‐like triple‐helical peptide with wild type α1 I and E317A mutant. The differential energetics observed for E317A are consistent with the HDX experiments and support a model in which intrinsically destabilized regions predispose conformational rearrangement in the integrin I domain. This study highlights the importance of exploring different timescales to delineate allosteric and binding events.